Comparative Efficacy of Foliar Silicon Application on Disease Reduction, Yield, and Nutrient Concentration of Wheat (Triticum aestivum L.) Under Blast Pathogen Stress (Journal of the Bangladesh Agricultural University, 2026)
Wheat blast, caused by Magnaporthe oryzae pathotype Triticum (MoT), is a destructive disease that can lead to significant or even total yield loss depending on how severe the infection was. Silicon-mediated disease tolerance is well-established in the literature. To evaluate the effect of Si on blast disease management, a pot experiment was conducted. The experiment utilized Randomized Complete Block Design (RCRD). The study included absolute control (Ta, no fertilizer), silicon-free control (T0), and silicon treatments. Silicon was applied as potassium silicate at 0.1% (T1), 0.2% (T2), and 0.3% (T3), and calcium silicate at 0.1% (T4), 0.2% (T5), and 0.3% (T6). Silicon fertilizers were applied as a foliar spray. The incidence and severity of blast disease were significantly reduced by silicon application across assessment points at 9, 11-, 13-, 15-, and 17-days post-inoculation. The maximum incidence (29%) and severity (62%) reduction was found in T6 treatment over the control. Silicon treatment significantly increases the yield contributing parameters and the yield of wheat. The highest yield was found at the T6 treatment. Again, Si concentration was also highest at the T6 treatment. Except for S, other nutrients (Ca, Mg, K, P, and B) concentration was significantly increased in different Si treatments, though the higher concentration slightly varied among different treatments in relation to different nutrients. Overall, CaSiO3 at a rate of 0.3% foliar spray showed a better performance than K2SiO3. So, CaSiO3 at a rate of 0.3% foliar spray could be an effective, eco-friendly input to manage wheat blast disease.J Bangladesh Agril Univ 24(2): 108–117, 2026